TANTANGAN BARU PENGAJARAN KESUSASTERAAN JEPANG DI INDONESIA - Idrus Idrus; Fithyani Anwar (Puitika, 2018)
In S1 Japanese Literature Study Program at the universities in Indonesia today, in addition to the general language competence, there are 3 main competencies namely linguistics, literature, and culture. The curriculum is then compiled with various lesson compositions to support these 3 competencies. Based on the research conducted in 2016-2017, the lessons for students in years 1 and 2 are generally focused on improving language skills. At the next level, the students are begun to be directed to the 3 fields mentioned earlier so that the final task in form of the thesis will adjust to the selected field of competencies. Teaching the literature of Japan on S1 Japanese Literature Study Program in Indonesia can be said to have not been well developed compared to the teaching of language or linguistic fields. The same thing happened with the studies that took the object of Japanese literature. Based on the results of the study, the main obstacle is the absence of Magister or doctoral program for this field in Indonesia so that the number of teachers with Japanese Literature background is still minimal when compared to the field of language education or Japanese Linguistics. In 2017, Kemristek DIKTI issued Permenristekdikti No 15 of 2017 concerning the adjustment of study program name according to the clusters of knowledge that give effect to S1 Japanese Literature Study Program throughout Indonesia. There are 4 choices, namely Japanese Language, Japanese Language and Culture, Japanese Literature, and Japanese Studies. This change made Study Program make several changes in accordance with the name while still prioritizing on the work prospects of graduates after graduation. This change 57 has become the major challenge for the development of Japanese Literature teaching and research in Indonesia. This paper aims to give an overview of Japanese Literature teaching at the university and the form of changes that have occurred in the current Japanese Literature teaching curriculum at the universities in Indonesia. Keywords: Curriculum, Japanese Department, Japanese Literature, Subject